Effects of the lower jaw position on athletic performance of elite athletes - Haughey, J. P.; Fine, P. (BMJ Open Sport & Exercise Medicine, 2020)
When an athlete wears a mouthguard, the position of the lower jaw is changed by virtue of the teeth being unable to occlude. Little research is available in in this area, which have indicated both positive impact and no positive impact.